Credit Risk Management and Profitability: A Study From Nepalese Commercial Bank - Shah, Miku; Vongbusin, Virachai (Nepalese Journal of Management Science and Research, 2019)
The main aim of the study is to investigate the impact of credit risk management on bank profitability in Nepalese commercial banks. Non-performing loan ratio, Leverage ratio, Capital adequacy ratio, Loan loss provision, Credit interest to credit facilities are independent variable whereas return on assets is dependent variable. Data has been collected from the Annual Reports of selected commercial banks, Banking and Financial Statistics and Bank Supervision Report published by Nepal Rastra Bank. The study is based on 25 samples making 250 observations. The independent study is completed using a blend of Independent t-test, Pearson’s Correction, analysis of variance (ANOVA), multiple regression analysis. The result shows that, capital adequacy ratio, leverage ratio, non-performing loan ratio, loan loss provision ratio is negative relationship to dependent variable return on assets. Likewise, credit interest to credit facilities is positively related to return on assets.